A technique for quality evaluation of e-learning from developers perspective - Abdellatief, Majdi; Md Sultan, Abu Bakar; A. Jabar, Marzanah; Abdullah, Rusli (Science Publications, 2011)
Problem statement: E-learning is gaining more acceptance as days pass because it provides learning opportunity any time and in any place. Different people have different preferences in terms of learning style such as reading text, listing audio or video, speaking and communication. To support these different learning preferences, there is need for multiple e-learning delivery methods and teaching techniques. Furthermore, there are many stakeholders of e-learning systems such as system developers, administrators, instructors, instructional designers, multimedia designers, online facilitators, independent evaluators. Whose views are important indicators for a complete e-learning system evaluation, but the most important views of e-learning quality are user view, developer’s view and manger’s view. Approach: The main aim of this study is to propose a new technique to evaluate e-learning website quality from developer’s view. To achieve our objective an extensive study on related resources was conducted. Our technique adopts the weights of quality characteristics which are obtained by carefully selected questionnaires’ from professional developers. We also present the evaluation process using AHP technique and the result of trial evaluation for validation of our technique Result: We proposed four quality characteristics named Service Content, System Functionality, Information Technology and System Reliability. We further, proposed 11 sub-characteristics with its attributes by following the structure of standard IOS/IEC 912. Conclusion: Our results show that the proposed technique could be useful and effective for ensuring that high quality systems are developed.